Tunable (violet to green) emission by high-yield graphene quantum dots and exploiting its unique properties towards sun-light-driven photocatalysis and supercapacitor electrode materials. (June 2017) - Kumar, Sumeet; Ojha, Animesh K.; Ahmed, Bilal; Kumar, Ashok; Das, Jayanta; Materny, Arnulf
Graphical abstract: Abstract: The precise control of dimension and mono-dispersibility of graphene quantum dots (GQDs) is still a challenge and new developments in this field are of great interest for scientific community. In this work, we have investigated the feasibility of the production of mono-dispersed spherical GQDs (∼4 nm) based on a treatment solely with ammonia solution as both, reducing and stabilizing agent. The structure, size and shape of the so synthesized GQDs were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM) and Raman spectroscopy measurements. The synthesized GQDs show excitation-dependent tunable color emission (violet to green). These GQDs could be potentially used as biomarkers for florescent bioimaging. The GQDs also prove to be excellent sunlight-driven photocatalysts for the photodegradation (45%) of methylene blue (MB) dye. Therefore, these GQDs could find remarkable application in the field of photocatalysis. Electrochemical measurements indicate good rate capability and stability of the GQDs in view of their use as supercapacitor electrode material. The present work not only provides a better explanation of the experimental observations, but also suggests an efficient method for the controllable synthesis of multi-functional GQDs.